Multiplatform observations of stratosphere-troposphere exchange over the Bharati (69.41° S, 76° E), Antarctica during ISEA-35. (December 2020) - Das, Siddarth Shankar; Ramkumar, Geetha; Koushik, N.; Murphy, D.J.; Girach, I.A.; Suneeth, K.V.; Subrahmanyam, K.V.; Soni, V.K.; Kumar, Vivek; Nazeer, M.
Abstract: This paper deals with the observations of stratospheric ozone intruding into the troposphere over the Bharati (69.41° S, 76.19° E) station in Antarctica, made during 35th Indian Scientific Expeditions to Antarctica (ISEA-35) during jet stream conditions. High-resolution multiplatform measurements from radiosonde coupled with ozonesonde, Very High-Frequency (VHF) radar and Micro-Limb Sounder (MLS) and Indian National Satellite System (INSAT-3D) satellite measurements are used for the present study. The most significant observation is that there is an increase of ozone by 30 ppbv in the upper troposphere and decrease by 100–110 ppbv in the lower stratosphere and this condition persisted for three successive days. The wind shows the presence of jet-stream in the vicinity of tropopause, enhancing the turbulence due to wind shear during the event of stratospheric intrusion. Further, the vertical velocity shows the presence of strong updrafts and downdrafts in the vicinity of tropopause which manifests the tropopause oscillation. Global analysis of satellite and reanalysis data also indicates the horizontal intrusion of stratospheric air from the mid-latitude to upper troposphere over the Bharati station. These observations constitute the first multi-instrumented, experimental evidence of stratospheric intrusions over the coastal Antarctica. These results are presented and discussed in the light of present understanding of turbulence and tropopause oscillation. Highlights: Stratosphere-troposphere exchange over Antarctica. Role of tropopause in stratospheric intrusion. Shear generated turbulence in the vicinity of tropopause.